(untitled) (Jurnal Yudisial, 2017)
ABSTRAK Putusan Nomor 2-3/PUU-V/2007 selain menjadi dasar konstitusionalitas pidana mati, juga memberikan jalan tengah (moderasi) terhadap perdebatan antara kelompok yang ingin mempertahankan (retensionis) dan yang ingin menghapus (abolisionis) pidana mati. Permasalahan dalam penelitian ini adalah bagaimana kebijakan moderasi pidana mati dalam putusan a quo dikaitkan dengan teori pemidanaan dan hak asasi manusia dan bagaimana kebijakan moderasi pidana mati dalam RKUHP tahun 2015 dikaitkan dengan putusan a quo. Penelitian ini merupakan penelitian doktrinal, dengan menggunakan bahan hukum primer dan sekunder, berupa peraturan perundang-undangan, literatur, dan hasil-hasil penelitian yang relevan dengan objek penelitian. Penelitian menyimpulkan, pertama, putusan a quo yang memuat kebijakan moderasi pidana mati telah sesuai dengan teori pemidanaan khususnya teori integratif dan teori hak asasi manusia di Indonesia di mana hak hidup tetap dibatasi oleh kewajiban asasi yang diatur dengan undang-undang. Kedua, model kebijakan moderasi pidana mati dalam RKUHP tahun 2015 beberapa di antaranya telah mengakomodasi amanat putusan a quo, seperti penentuan pidana mati di luar pidana pokok, penundaan pidana mati, kemungkinan pengubahan pidana mati menjadi pidana seumur hidup atau penjara paling lama 20 tahun. Selain itu masih menimbulkan persoalan berkaitan dengan lembaga yang memberikan pengubahan pidana mati, persoalan grasi, lamanya penundaan pelaksanaan pidana mati, dan jenis pidana apa saja yang dapat diancamkan pidana mati. Kata kunci: kebijakan, KUHP, moderasi, pidana mati. Â ABSTRACT Constitutional Courtâ€™s Decision Number 2-3/PUU-V/2007, in addition to being the basis of theÂ constitutionality of capital punishment, also providesÂ a moderate way of arguing between retentionistÂ groups and those wishing to abolish the death penaltyÂ (abolitionist). The problem in this research is howÂ the moderation policy of capital punishment in aquoÂ decision is associated with the theory of punishmentÂ and human rights and how the moderation policy ofÂ capital punishment in the draft Criminal Code of 2015Â (RKUHP) is related with the a quo decision. This study isÂ doctrinal, using primary and secondary legal materials,Â in the form of legislation, literature and research resultsÂ that are relevant to the object of analysis. This studyÂ concludes, firstly, the aquo decision containing theÂ moderation policy of capital punishment has been inÂ accordance with the theory of punishment, specificallyyÂ the integrative theory and the theory of human rights inÂ Indonesia, in which the right to life remains limited by theÂ fundamental obligations set forth in the law. Secondly,Â some of the modes of moderation model of capitalÂ punishment in RKUHP of 2015 have accommodated theÂ mandate of aquo decision, such as the determinationÂ of capital punishment outside the main punishment,Â postponement of capital punishment, the possibility ofÂ converting capital punishment to life imprisonment orÂ imprisonment of 20 years. In addition, it still raises issuesÂ regarding the institutions that provide for conversion ofÂ capital punishment, pardon matters, length of delay inÂ the execution of capital punishment, and any types ofÂ crime punishable by capital punishment.Â Keywords: policy, criminal code, moderation, capitalÂ punishment.